Factors associated with aspirin resistance in diabetic patients: A metabolic and inflammatory profile analysis - Bo Chen; Zisheng Li; Jianyong Zhao; Huamei Dong; Long Tong; Jiaqing Dou (PLoS ONE, 2025)
Background Diabetes mellitus (DM) is strongly linked to both first-time and recurrent atherosclerotic thrombotic events. Although aspirin (ASA) is commonly used to prevent cardiovascular diseases, studies have shown that ASA does not significantly reduce the risk of cardiovascular events in DM patients. This inconsistency highlights the need for further research into the underlying mechanisms of ASA resistance. Therefore, this study investigates the factors associated with aspirin resistance in DM patients, aiming to offer insights for improving cardiovascular disease prevention in this group. This study specifically investigated biochemical aspirin resistance, defined as inadequate suppression of thromboxane biosynthesis. Methods This prospective case-control study enrolled 53 DM patients and 66 age-/sex-matched healthy controls. Baseline metabolic-inflammatory markers—including BMI, LDL-C, cystatin C (CysC), hs-CRP, and HOMA-IR—were assessed alongside urinary 11-dehydrothromboxane B2 (11dhTxB2) levels pre- and post-aspirin intervention (81–100 mg/day × 7 days). Biochemical aspirin resistance was defined as post-administration urinary 11dhTxB2 ≥ 1500 pg/mg creatinine, reflecting inadequate suppression of total body thromboxane biosynthesis. Group comparisons utilized nonparametric tests (Mann-Whitney U) for skewed variables and χ2 tests for categorical data. The influencing factors of ASA resistance were investigated through univariate analysis and logistic regression analysis, with multiple linear regression analysis being applied to model the Δ11dhTxB2 (post- vs. pre-administration difference). Results Compared to age-/sex-matched controls, diabetic patients exhibited significantly elevated metabolic-inflammatory markers (BMI, LDL-C, CysC, hs-CRP, HOMA-IR; all P < 0.01) and 60% higher baseline urinary 11dhTxB2 levels (2,324.58 vs. 1,452.51 pg/mg creatinine; P = 0.001), with persistent post-ASA disparity (1,205.31 vs. 1,058.02 pg/mg creatinine; P = 0.007). Biochemical aspirin resistance prevalence was 2.7-fold higher in diabetes (20.8% [11/53] vs. 7.6% [5/66]; P = 0.036). Univariate analysis linked Pre-11dhTxB2,higher BMI, hs-CRP, and HOMA-IR to ASA resistance (all P < 0.05), though multivariable logistic regression showed nonsignificant trends. Logistic regression analysis revealed that each unit increase in baseline 11dhTxB2 was associated with a 0.2% increase in the odds of aspirin resistance. Multivariable linear regression identified systemic inflammation (hs-CRP: B = 2,147.6, P < 0.001) and higher BMI (BMI: B = 204.9, P = 0.021) were strongly associated with attenuated thromboxane suppression (Δ11dhTxB2). Conclusion Patients with diabetes exhibit heightened thromboxane biosynthesis and a markedly elevated prevalence of biochemical aspirin resistance compared to healthy individuals, underscoring a prothrombotic phenotype linked to metabolic-inflammatory dysregulation. Higher BMI and systemic inflammation emerged as key factors associated with attenuated aspirin efficacy, suggesting platelet activation pathways beyond conventional COX-1 inhibition or involving non-platelet sources. Early identification of platelet hyperreactivity, coupled with targeted metabolic control and anti-inflammatory strategies, may refine personalized cardiovascular prevention in this high-risk population,while acknowledging that persistent urinary 11dhTxB2 elevation post-aspirin likely reflects significant non-platelet thromboxane generation.